Pedra Branca judgment and beyond: issues and challenges in its implementation by Malaysia and Singapore - Hamid, Abdul Ghafur@Khin Maung Sein (Martinus Nijoff Publishers/Brill, 2011)
The recent judgment of the ICJ in the Pedra Branca case is of crucial importance to Singapore and Malaysia because having resolved the question of which State has sovereignty over Pedra Branca and Middle Rocks, the Court has paved the way for the resolution of the delimitation of the maritime boundaries between the two States. However, this matter, as does South Ledge’s legal status, still needs to be further worked out by the “Joint Technical Committee” the two States have subsequently set up for the purpose. Moreover, the Court’s judgment and subsequent decisions of the Technical Committee affect the exercise of sovereign rights in those waters such as the conduct of naval patrols, navigational aids, protection of the marine environment and the exploitation of natural resources. Another vital complexity is how Indonesia’s maritime rights generated by its islands in the Straits of Singapore will be negotiated with Singapore and Malaysia.